Policy Contexts of Social Work in Britain: the Wider Implications of ‘New’ Labour Policy and the ‘New Legal Regime’ - Sue Penna (Social Work and Society)
Several commentators have expressed disappointment with New Labour’s apparent adherence to the policy frameworks of the previous Conservative administrations. The employment orientation of its welfare programmes, the contradictory nature of the social exclusion initiatives, and the continuing obsession with public sector marketisation, inspections, audits, standards and so on, have all come under critical scrutiny (c.f., Blyth 2001; Jordan 2001; Orme 2001). This paper suggests that in order to understand the socio-economic and political contexts affecting social work we need to examine the relationship between New Labour’s modernisation project and its insertion within an architecture of global governance. In particular, membership of the European Union (EU), International Monetary Fund (IMF) and World Trade Organisation (WTO) set the parameters for domestic policy in important ways. Whilst much has been written about the economic dimensions of ‘globalisation’ in relation to social work rather less has been noted about the ways in which domestic policy agenda are driven by multilateral governance objectives.